Field Science—the Nature and Utility of Scientific Fields - Arturo Casadevall (American Society for Microbiology, 2015)
ABSTRACT Fields are the fundamental sociological units of science. Despite their importance, relatively little has been written about their emergence, composition, structure, and function in the scientific enterprise. This essay considers the nature of fields and their important role in maintaining information and providing normative standards for scientific work. We suggest that fields arise naturally as a consequence of increasing information and scientific specialization. New fields tend to emerge as research communities grow, which may reflect biologically determined optima for the size of human groups. The benefits of fields include the organization of scientists with similar interests into communities that collectively define the next important problems to pursue. In the discipline of microbiology, fields are often organized on the basis of phylogenetic differences between microorganisms being studied. Although fields are essential to the proper functioning of science, their emergence can restrict access by outsiders and sustain dogmas that hinder progress. We suggest mechanisms to improve the functioning of scientific fields and to promote interdisciplinary interaction between fields.